Ecological value of wood energy plantations in the support of some animal groups - Szabó, Fruzsina Magdolna; Juhász, Lajos (Acta Agraria Debreceniensis, 2023)
Today, some environmental problems have reached such severe proportions that it is no longer enough to recognise them, but environmentally friendly solutions must be used to reduce them. The reduction in the area of natural forests of native species is causing problems in several ways. This research aimed to highlight how environmental, conservation and economic interests can be reconciled. In addition to natural forests, wood energy plantations are becoming increasingly important. Energy import dependency is a problem for most countries, for which wood energy plantations can partly offer an alternative. Native forests can be protected, and their area increased where possible. Meanwhile, energy plantations can be established in areas with low agricultural productivity. In this experiment, I studied a plantation of Pedunculate Oak (Quercus robur), a Black Locust (Robinia pseudoacacia) and a Paulownia (Paulownia Shan Tong). I selected burrowing birds and ground-dwelling arthropods as indicator groups. I did this by establishing a nesting colony and soil trapping. I wanted to demonstrate that, in addition to natural forests, wood energy plantations have a role not only in economic terms but also in maintaining certain animal groups. Soil trapping tests were carried out in all three tree plantations. The obtained results showed that in the Paulownia plantation, the occupancy rate of nest boxes was almost 100%, while in the Black Locust plantation it was around 30%. Among the species that occupied the nesting sites, the Common Starling (Sturnus vulgaris) and the Eurasian Tree Sparrow (Passer montanus) were more abundant, while Great Tit (Parus major) was present in the Black Locust plantation. These are opportunistic species for which nesting opportunity is the most important factor, since their feeding area (in the case of the Common Starling and the Eurasian Tree Sparrow) is not typical of the nesting area. The soil trap investigations show that there are no significant differences in the composition of the arthropod group (beetles, spiders) in the study areas.